CHANGES OF SPECIFIC INDICES OF PROOXIDATIVE AND ANTIOXIDANT SYSTEMS IN TIMUS OF ANIMALS IN EXPERIMENTAL ALERGETIC ALVEEOLITE IN STRESS CONDITIONS AND THEIR CORRECTION - Kovalska, M.Ye.; Zhukovsky, V.S.; Baida, M.L. (World of Medicine and Biology, 2019)
The performed studies showed that in the experimental AA before treatment with Corvitin, the processes of lipid peroxidation and antioxidant system in the thymus are activated, the results of the experimental AA model before treatment with Corvitin give grounds to assert the development of the imbalance between the prooxidant and antioxidant systems, in particular the gradual suppression of the antioxidant defense of the body in female guinea pigs and significant activation of lipid peroxidation processes in the experimental AA before treatment with Corvitin. To correct LPO and AOS parameters in group VIII of the experimental AA model under the conditions of immobilization stress (thirty-fourth day) treatment with Corvitin was carried out, which was administered intraperitoneally at the dose of 40 mg / kg (the drug “Corvitin”, Borshchagovsky Chemical-Pharmaceutical Plant), which led to the decrease in the formation of lipid peroxidation and AOS products in the thymus, having decreased compared to animals with the combined pathology, which were injected with the antioxidant Corvitin. The obtained research results allow us to speak about the corrective effect of Corvitin on the indices of the prooxidant and antioxidant systems in the thymus during experimental AA under conditions of immobilization stress and make it possible to recommend this antioxidant for further studies.
Keywords: experimental allergic alveolitis; immobilization stress; thymus; corvitin